2018
DOI: 10.1111/jse.12443
|View full text |Cite
|
Sign up to set email alerts
|

Fruit fossils of Rosoideae (Rosaceae) from the late Pliocene of northwestern Yunnan, Southwest China

Abstract: The subfamily Rosoideae Focke (Rosaceae) has a good fossil record in the Northern Hemisphere, but these fossil records are confined mainly to a few genera, whereas the majority, in particular those with herbaceous members, are still under‐represented. In this study, we describe new fruit fossils of Rosoideae, including Fragaria achenes and Rubus endocarps, from the late Pliocene of northwestern Yunnan, Southwest China. These fossils add new accounts to the fossil archive of Rosoideae and provide the first foss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 50 publications
(75 reference statements)
1
14
0
1
Order By: Relevance
“…We also estimated the age of divergences across the Fragaria phylogeny, using five fossils that possess synapomorphies of their respective clades as crown group calibrations (34)(35)(36), including the minimum age (2.9 Mya) for the root node of the north clade. Furthermore, a newly discovered achenes fossil of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also estimated the age of divergences across the Fragaria phylogeny, using five fossils that possess synapomorphies of their respective clades as crown group calibrations (34)(35)(36), including the minimum age (2.9 Mya) for the root node of the north clade. Furthermore, a newly discovered achenes fossil of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fragaria from the late Pliocene (2.6 to 3.6 Mya) in Yunnan, Southwest China (36) suggested that the south clade, at least, had originated before 2.6 Mya (the minimum age for the root node of the south clade). Based on these fossils, our estimate of the origin of Fragaria, 7.94 (6.5 to 10.3) Mya (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al () report on distinctive fossil endocarps of Fragaria and Rubus (Rosaceae, subfamilies Rosoideae) from northwestern Yunnan, Southwest China. This discovery indicates that these genera, which are diverse in the same region today, were already part of the flora in the late Pliocene.…”
mentioning
confidence: 99%
“…By comparison with the conditions in which extant Christella occurs, the authors infer that the Liuqu flora was deposited prior to major uplift in a warm humid habitat significantly lower in elevation than today. Huang et al (2019) report on distinctive fossil endocarps of Fragaria and Rubus (Rosaceae, subfamilies Rosoideae) from northwestern Yunnan, Southwest China. This discovery indicates that these genera, which are diverse in the same region today, were already part of the flora in the late Pliocene.…”
mentioning
confidence: 99%